2022
DOI: 10.3389/fendo.2022.818272
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of the Circadian Transcription Factor BMAL1 in Reproductive Endocrinology and Fertility

Abstract: Brain and muscle aryl-hydrocarbon receptor nuclear translocator like protein1 (BMAL1), a core component of circadian oscillation, is involved in many physiological activities. Increasing evidence has demonstrated the essential role of BMAL1 in reproductive physiology. For instance, BMAL1-knockout (KO) mice were infertile, with impaired reproductive organs and gametes. Additionally, in BMAL1-KO mice, hormone secretion and signaling of hypothalamus-pituitary-gonadal (H-P-G) hormones were also disrupted, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 118 publications
(238 reference statements)
1
12
0
1
Order By: Relevance
“…Furthermore, Bmal1 knockout was found to induce ovarian dysplasia, significantly reduce follicle and corpora lutea counts, and impair steroid production in female mice. In Bmal1 knockout male mice, testes, seminal vesicles, and seminiferous tubules are generally reduced in diameter [ 23 25 ]. These results suggest a key role for Bmal1 in reproductive endocrinology and fertility, although we lack an understanding of the underlying mechanisms.…”
Section: Overview Of Bmal1mentioning
confidence: 99%
“…Furthermore, Bmal1 knockout was found to induce ovarian dysplasia, significantly reduce follicle and corpora lutea counts, and impair steroid production in female mice. In Bmal1 knockout male mice, testes, seminal vesicles, and seminiferous tubules are generally reduced in diameter [ 23 25 ]. These results suggest a key role for Bmal1 in reproductive endocrinology and fertility, although we lack an understanding of the underlying mechanisms.…”
Section: Overview Of Bmal1mentioning
confidence: 99%
“…This study demonstrated that mice lacking BMAL1 expression in the uterus can implant embryos but not sustain a pregnancy. The previous studies showed the possible involvement of Bmal1 in regulation of male and female reproductive functions [ 31 , 32 , 33 ]. It was shown that systemic Bmal1 KO female mice can ovulate but both embryo development and ovarian production of progesterone (P4) are not enough to achieve embryo implantation [ 10 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Theca cells are the pacemakers that regulate ovulation timing and transient sensitivity to LH [ 14 ]. In these conditional knockout mice, transient susceptibility to LH was found in littermate controls and granulosa cell-specific Bmal1 knockout mice, but not in theca cell-specific Bmal1 knockouts [ 7 , 74 ]. This indicated that follicle development and ovulation are affected by circadian rhythm disfunction in theca cells ( Table 1 ).…”
Section: Effects Of the Circadian Clock On The Hypothalamic–pituitary...mentioning
confidence: 99%